Modelling the role of personal factors as mediators in the relationship between workplace stress, motivation and job performance among Irish retail employees. (2018) - McGuigan, Charles John; McGuigan, Karen; McGuigan, Maria; Shevlin, Mark; Mallett, John; Tracey, Anne
This study explores the mediating role of personal factors in the relationship between workplace stress, motivation and performance to elucidate the mechanisms through which workplace factors affect job performance. Irish retail employees (N = 420) completed measures of workplace stress, motivation, job satisfaction, innovation, coping, resilience and job performance. Three alternative models were specified with the relationship between workplace factors and job performance described as either: 1) direct only; 2) indirect only; 3) both direct and indirect. Model fit for each was assessed with the indirect only model the best fit. Results show a significant indirect effect of workplace stress on job performance through task orientated coping (β = 0.030, p < 0.05), and significant indirect effects of work motivation on job performance through innovation (β = 0.046, p > 0.05) and task orientated coping (β = 0.021, p < 0.05). The findings offer insight into the mechanisms by which workplace factors impact longer-term job performance.